Breaking out of the deficit trap: The case against the fiscal hawks - James K. Galbraith (Levy Economics Institute of Bard College, 2005)
For some time, Levy Institute scholars have been engaged with issues related to the current account, government, and private sector balances. We have argued that the existing imbalances in these accounts are unsustainable and will ultimately present a serious challenge to the performance of the American economy. Other scholars are also concerned, but for reasons that we do not share. They argue that the interest rate is determined by the supply and demand of saving. When the government reduces its saving, the total supply of saving falls, and the interest rate inevitably rises. The result, they say, is that interest-sensitive spending, and investment in particular, falls. Finally, these scholars say, less investment now necessarily implies less output in the future. In this new brief, Senior Scholar James K. Galbraith evaluates a recent article by William G. Gale and Peter R. Orszag, two economists who regard this view of deficits as plausible. He forwards an alternative, Keynesian view. This alternative suggests that deficits can increase overall output, possibly enabling the government to spend more money without increasing the ratio of the debt to GDP. He casts doubt on the notion that the interest rate is determined by the supply and demand of saving, arguing that monetary policy plays a much larger role than Gale and Orszag allow for. Moreover, he writes, strong demand for goods and services is more important than the supply of capital in determining the pace of technological advance and the rate of growth of output per worker.
Keywords: 330; Öffentliche Schulden; Auslandsverschuldung; Ricardianisches Äquivalenztheorem; Wirtschaftspolitik; Haushaltskonsolidierung; USA